Effects of particle size on determination of the contents of grain and legume dietary fibre and resistant starch - Blaž FERJANČIČ; Mojca KOROŠEC; Saša PISKERNIK; Jasna BERTONCELJ (Acta Agriculturae Slovenica)
Dietary fibre comprises non˗digestible carbohydrates, including resistant starch, and lignin, and it is an important constituent of a healthy diet. The aim was to define the influence of particle size on contents determined for dietary fibre and resistant starch in unprocessed grain and canned legumes. Five samples of unprocessed and processed grains were analysed, as oatmeal, buckwheat, dehulled barley, wheat and spelt, and three canned legumes, as beans, chickpeas and peas, with and without their brine. Samples were initially milled unscreened, and then again through 500 μm or 350 μm screens. For unprocessed grain samples, there was generally no influence of particle size, except for the 350-μm milling of dehulled barley, with significantly decreased contents determined for insoluble dietary fibre and resistant starch presumably due to damaging of starch granules and disrupting crystalline formation of starch. For canned legumes with and without their brine, particle size had little effect on contents determined for dietary fibre and resistant starch.